Haemodynamic Responses Following Lidocaine Infusion on Hypertensive Patient Undergoing Laparoscopic Cholecystectomy (Community Based Medical Journal, 2024)
Many pharmacological methods have been evaluated to attenuate the adverse haemodynamic responses resulting from airway manipulation and pneumoperitoneum. Intravenous lidocaine infusion is one of them; bolus dose of intravenous lidocaine is used to reduce haemodynamic changes resulting from intubation and extubation reflex whereas intraoperative infusion of lidocaine has been used for post-operative analgesia in laparoscopic cholecystectomy. This randomized controlled trial was conducted to observe the effectiveness of lidocaine infusion in obtundation of haemodynamic responses on hypertensive patient undergoing laparoscopic cholecystectomy. A total number of 80 patients were enrolled in this study. Patients were allocated into two groups by computer generated random chart according to a 1:1 ratio. The patients of group A were given general anaesthesia with placebo normal saline infusion and the patients of group B were given general anaesthesia with lidocaine infusion (1.5mg/kg). Mean differences of blood pressure (SBP & MAP) and heart rate at different time periods from baseline were compared between two groups. The demographic profiles were almost similar between the groups (p>0.05). In comparison between two groups, heart rate, systolic blood pressure and mean arterial pressure rise from baseline value was more in normal saline group (group A) than lidocaine test group (group B) during peri-intubation, pneumoperitoneum and peri-extubation period. Statistical difference was significant between two groups (p